The association between nutritive, non-nutritive sucking habits and primary dental occlusion - Hiu Tung Bonnie Ling; Fung Hou Kumoi Mineaki Howard Sum; Linkun Zhang; Cindy Po Wan Yeung; Kar Yan Li; Hai Ming Wong; Yanqi Yang (BMC, 2018)
Abstract Background The development of primary dentition can be affected by oral sucking habits. Therefore, this study aims to investigate the association of nutritive and non-nutritive sucking habits with primary dentition development. Methods One thousand one hundred and fourteen children aged 2 to 5 years old in Hong Kong were recruited in a cross-sectional study. Information on their nutritive (e.g. breastfeeding and bottle feeding) and non-nutritive sucking habits (e.g. pacifier use and thumb/digit sucking) was collected via questionnaires. The children's primary occlusions were examined in three dimensions. Results Children who were breastfed for more than 6 months had a lower proportion of daily pacifier use (p < 0.05). Children who used pacifiers daily had a higher proportion of thumb/digit sucking (p < 0.05). Children who used pacifiers daily for more than one year had higher chances of developing an anterior open bite (p < 0.05) and a reduced overbite (p < 0.05). Those exhibiting daily thumb/digit sucking for more than one year had higher chances of developing Class II incisor and Class II canine relationships, an increased overjet and anterior open bite (p < 0.05). Conclusion Pure breastfeeding for more than 6 months is inversely associated with daily pacifier use and daily pacifier use is positively associated with daily thumb/digit sucking. Children with more than one year of daily pacifier use and thumb/digit sucking have higher chances of developing abnormal dental relationships in the sagittal (i.e. Class II incisor and Class II canine relationships and increased overjet) and vertical (i.e. anterior open bite) dimensions, respectively.